Genetic Characterization of Antibiotic-Resistant Staphylococcus spp. and Mammaliicoccus sciuri from Healthy Humans and Poultry in Nigeria - Christiana Jesumirhewe; Tolulope Oluwadamilola Odufuye; Juliana Ukinebo Ariri; Amdallat Arike Adebiyi; Amina Tanko Sanusi; Anna Stöger; Beatriz Daza-Prieto; Franz Allerberger; Adriana Cabal-Rosel; Werner Ruppitsch (MDPI AG, 2024)
Staphylococcus spp. poses a significant threat to human and animal health due to their capacity to cause a wide range of infections in both. In this study, resistance genes conferring antibiotic resistance in Staphylococcus spp. and Mammaliicoccus sciuri isolates from humans and poultry in Edo state, Nigeria, were investigated. In April 2017, 61 Staphylococcus spp. isolates were obtained from urine, wounds, nasal and chicken fecal samples. Species identification was carried out by matrix-assisted laser desorption ionization-time of flight mass spectrometry. Antimicrobial susceptibility testing was performed using the Kirby-Bauer method for 16 antibiotics. Whole-genome sequencing was used for characterization of the isolates. The 61 investigated isolates included Staphylococcus aureus, S. arlettae, M. sciuri, S. haemolyticus, and S. epidermidis. A total of 47 isolates (77%) belonged to human samples and 14 (23%) isolates were collected from poultry samples. All were phenotypically resistant to at least three antimicrobial(s). Multiple resistance determinants were detected in the human and poultry isolates analyzed. Phylogenetic analysis revealed close relatedness among the isolates within each species for S. arlettae, M. sciuri, and S. haemolyticus, respectively. This study delivered comprehensive genomic insights into antibiotic-resistant Staphylococcus species and M. sciuri isolates from human and poultry sources in Edo state, Nigeria, from a One Health perspective.